Duncan, Dawn. Irish Myth, Lore and Legend on Film - Bolfarine, Mariana (ABEI Journal, 2013)
Duncan, Dawn. Irish Myth, Lore and Legend on Film. Reimagining Ireland, Vol. 27. Bern: Peter Lang, 2013. 171 pp.